Single Nucleotide Polymorphisms of EXOC1, BCL2, CCAT2, and CARD8 Genes and Susceptibility to Cervical Cancer in the Northern Chinese Han Population - Feng, Yanan; Wang, Zhenzhen; Zhu, Manning; Li, Songxue; Dong, Shuang; Gong, Liping; Li, Xiaoying; Zhang, Shuang; Jia, Tianshuang; Kong, Xianchao; Tian, Jiawei; Sun, Litao (Frontiers in Oncology, 2022)
Cervical cancer (CC) is one of the main malignant tumors that threaten the health and lives of women around the world, and its morbidity and mortality rate ranks fourth. At present, most studies on the genetic background of CC focus on genetic polymorphisms. Single nucleotide polymorphisms (SNPs) are considered clinically as potential diagnostic and therapeutic biomarkers for a variety of tumors. Therefore, we aimed to explore the association between SNPs in different genes (EXOC1 gene, BCL2 gene, CCAT2 gene and CARD8 gene) and susceptibility to CC. This study is a case-control study based on women in northern Chinese, which included 489 women with CC and 513 healthy women. This study used multiplex PCR combined with next-generation sequencing to genotype the selected SNPs (rs13117307(C/T) in EXOC1 gene, rs2279115(C/A) in BCL2 gene, rs6983267(G/T) in CCAT2 gene and rs7248320(G/A) in CARD8 gene). The results of the study showed that there was no significant association between the four SNPs and the susceptibility to CC. However, in further stratified analysis, we found that rs13117307 and rs2279115 were significantly related to SCC levels in women with CC, and rs6983267 was significantly related to the menopausal status of women with CC. Specifically, alleles T of rs13117307 and genoytpe AA of rs2279115 when SCC is greater than 0.5 ng/ml will increase the risk of CC. The genotype TG/TG+TT of rs6983267 increases the risk of CC in premenopausal women. Therefore, we speculate that EXOC1, BCL2, and CCAT2 genes may be involved in the occurrence and development of CC, we have a deeper understanding of the pathogenesis of CC.